The impact of control styles and control modes on individual-level outcomes: a first test of the integrated IS project control theory. Issue 2 (3rd March 2020) - Remus, Ulrich; Wiener, Martin; Saunders, Carol; Mähring, Magnus
ABSTRACT: While IS development (ISD) projects are essential for deploying digital technologies in organisations, they are notoriously challenging to control and complete successfully. Prior ISD project control research mostly conceptualises control activities in terms of formal and informal control modes and frequently focuses on performance effects at the project level. We argue that new insight can be gained by moving beyond these conventions to include control enactment as well as individual-level control effects. In this study, we present new findings that could precipitate a change in how researchers think about, and practitioners exercise, control in ISD projects. Specifically, we provide a first test of the recently proposed Integrated IS Project Control Theory by analysing the impacts of control modes (what) and control styles (how) on project team members' task performance and job satisfaction. Employing data from 171 ISD projects, we find significant support for this theory by confirming the positive impact of an enabling control style on both task performance and job satisfaction, and by demonstrating that control style is more important than control modes in explaining individual-level control effects. Further, the results of a post-hoc analysis suggest complex interaction effects between an enabling control style and formal controls.